Tinjauan Komprehensif Mastitis pada Ternak Perah: Analisis Etiologi, Strategi Pencegahan, serta Implikasinya terhadap Produktivitas Susu dan Ekonomi Peternak: A Comprehensive Review of Mastitis in Dairy Cattle: Etiological Analysis, Prevention Strategies, and Implications for Milk Productivity and Farmer Economy - Ine Karni; Rezki Amalyadi; Aminurrahman; Ica Ayu Wandira; I Gede Nano Septian; Zaid Al Gifari; Khairil Anwar; Muhammad Dohi (Universitas Muhammadiyah Palu, 2025)
The dairy industry plays a strategic role in providing animal food, especially milk and its processed products. However, the sustainability of this industry is faced with the challenge of disease, one of which is mastitis inflammation of the udder which is generally caused by bacterial infections such as Staphylococcus aureus, Streptococcus agalactiae, and Escherichia coli. Mastitis is divided into clinical and subclinical forms, with significant impacts on livestock health, animal welfare, decreased milk production and quality, and economic losses for farmers. This study aims to examine the causes of mastitis, its risk factors, and prevention and control strategies at the farm level. The method used is a literature study of various scientific sources and current publications. The results of the study indicate that controlling mastitis requires a holistic approach through hygienic milking practices, good barn management, application of dry cow therapy, chronic culling of dairy cattle, vaccination, and regular monitoring of udder health. Implementation of sustainable prevention strategies, accompanied by increased farmer awareness and policy support, is key to reducing the prevalence of mastitis and strengthening the resilience of dairy farming businesses.